How to achieve ISO 9000 registration economically and efficiently - Naroola, Gurmeet (Quality and reliability, 1996)
Adopting a hands-on approach, this work shows how to achieve ISO 9000 registration efficiently and economically, through the TAP-PDSA (Train, Audit and Plan / Plan, Do, Study, Act) method. It explains issues encountered in registering, providing real examples, and addresses the functions of a registrar, the importance of choosing a registrar early, and the criteria of registrar selection. The primary goals of registration - to improve quality, achieve customer satisfaction and increase profitability - are stressed.